Hypothyroidism correlates with favourable survival prognosis in patients with brain metastatic cancer. (August 2020) - Berghoff, Anna S.; Wippel, Christoph; Starzer, Angelika M.; Ballarini, Nicolas; Wolpert, Fabian; Bergen, Elisabeth; Wolf, Peter; Steindl, Ariane; Widhalm, Georg; Gatterbauer, Brigitte; Marosi, Christine; Dieckmann, Karin; et al.
Abstract: Background: Several preclinical and epidemiologic studies have indicated tumour-promoting effects of thyroid hormones (THs). However, very limited knowledge exists on the prognostic impact of thyroid function in metastatic cancer. Methods: We compiled a discovery cohort of 1692 patients with newly diagnosed brain metastases (BMs) of solid cancers treated at the Medical University of Vienna and an independent validation cohort of 191 patients with newly diagnosed BMs treated at the University Hospital Zurich. Results: Hypothyroidism before diagnosis of cancer was evident in 133 of 1692 (7.9%) patients of the discovery, and in 18 of 191 (9.4%) patients of the validation cohort. In the discovery cohort, hypothyroidism was statistically significantly associated with favourable survival prognosis from diagnosis of cancer (31 vs. 21 months; p = 0.0026) and with survival prognosis from diagnosis of BMs (12 vs. 7 months; p = 0.0079). In multivariate analysis including the diagnosis-specific graded prognostic assessment score, primary tumour type and sex, hypothyroidism was an independent factor associated with survival after diagnosis of BMs (hazard ratio: 0.76; 95% confidence interval [CI]: (0.63; 0.91; p = 0.0034). In the validation cohort, the association of hypothyroidism and favourable survival prognosis from diagnosis of cancer (55 vs. 11 months; p = 0.00058), as well as from diagnosis of BMs (40 vs. 10 months; p = 0.0036) was confirmed. Conclusion: Pre-existing hypothyroidism was strongly and independently associated with prognosis in patients with newly diagnosed BMs, supporting the evidence from preclinical data that THs may indeed have a tumour-promoting effect. Further investigation of the underlying pathobiological mechanism and potential therapeutic implications are required. Highlights: Association of thyroid function and prognosis was analysed in a discovery cohort patients with newly diagnosed brain metastases (BMs) and an independent validation cohort. Hypothyroidism was associated with increased survival from primary tumour, as well as from BMs diagnosis. Hyperthyroidism was less frequently observed and not observed with clinical characteristics.